Silicone-Acyclovir Controlled Release Devices Suppress Primary Herpes Simplex Virus-2 and Varicella Zoster Virus Infections In Vitro - Carol L. Berkower; Nicole M. Johnson; Stephen B. Longdo; Shenika O. McGusty-Robinson; Samantha L. Semenkow; Barry J. Margulies (Hindawi Limited, 2013)
Following initial infection, herpesviruses retreat into a permanent latent state with periodic reactivation resulting in an enhanced likelihood of transmission and clinical disease. The nucleoside analogue acyclovir reduces clinical symptoms of the three human alpha herpesviruses, HSV-1, HSV-2, and VZV. Long-term administration of acyclovir (ACV) can reduce the frequency and severity of reactivation, but its low bioavailability and short half-life require a daily drug regimen. Our lab is working to develop a subcutaneous delivery system to provide long-lasting, sustained release of ACV. Previously, we demonstrated that an implantable silicone (MED-4050) device, impregnated with ACV protected against HSV-1 both in vitro and in vivo. Here, we extend our in vitro observations to include protection against both HSV-2 and VZV. We also demonstrate protection against HSV-2 in vitro using MED-4750, a silicone polymer designed for long-term use in humans. When release of ACV from MED-4750 is quantitated on a daily basis, an initial burst of 5 days is observed, followed by a long period of slow release with near-zero-order kinetics, with an average daily release of 1.3923 ± 0.5908 μg ACV over days 20-60. Development of a slow-release implant has the potential to significantly impact the treatment of human alpha herpesvirus infections.